Green Economy-Based Tourism Village Development Strategy in Denai Lama Village, Deli Serdang - Ilham Habibi Lubis; Maryam Batubara; Muhammad Arif (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to find out how the main priority strategy for the development of a Green Economy-based tourism village in Denai Lama Village, Deli Serdang, is by presenting the internal and external conditions that have been carried out so far. Then in addition, the researcher also explained some of the handling urgency that needs to be implemented so that the development of Green Economy-based tourist villages can be more focused. The method used is a qualitative method using SWOT analysis and QSPM. The number of respondents who filled out the questionnaire was 5 respondents from SMEs in the market and 5 respondents from experts. Based on the results of the SWOT analysis, the strategy quadrants obtained after being processed in the IFE and EFE matrices are in Quadrant I. This indicates that the strategy used is a progressive strategy. This strategy means that tourism villages have strengths and opportunities. Furthermore, in the QSPM analysis, the results show that the main priority strategy that must be carried out is to make the entertainment of native Indonesian art a characteristic of your market so that it attracts the attention of local and foreign tourists.